2020
DOI: 10.1016/j.nicl.2020.102327
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive characterization of amyotrophic lateral sclerosis in a hTDP-43A315T mouse model: A PET-MR study

Abstract: Currently TAR DNA binding protein 43 (TDP-43) pathology, underlying Amyotrophic Lateral Sclerosis (ALS), remains poorly understood which hinders both clinical diagnosis and drug discovery efforts. To better comprehend the disease pathophysiology, positron emission tomography (PET) and multi-parametric magnetic resonance imaging (mp-MRI) provide a non-invasive mode to investigate molecular, structural, and neurochemical abnormalities in vivo . For the first time, we report the findings of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In the spinal cord, glucose metabolism appeared to be reduced at early symptomatic and end stages of the disease in SOD1 G93A mice, but was increased before disease onset [96]. Recently, Weerasekera et al used simultaneous 18 F-FDG PETmagnetic resonance imaging and showed that glucose metabolism is decreased in the motor and somatosensory cortices of TDP-43 A315T mice while it was increased in midbrain region between 3 and 7 months of age, as compared to WT controls [97]. This suggests that similar changes in glucose metabolism may be observed across ALS disease models.…”
Section: Alterations In Glucose Transport or Utilizationmentioning
confidence: 99%
“…In the spinal cord, glucose metabolism appeared to be reduced at early symptomatic and end stages of the disease in SOD1 G93A mice, but was increased before disease onset [96]. Recently, Weerasekera et al used simultaneous 18 F-FDG PETmagnetic resonance imaging and showed that glucose metabolism is decreased in the motor and somatosensory cortices of TDP-43 A315T mice while it was increased in midbrain region between 3 and 7 months of age, as compared to WT controls [97]. This suggests that similar changes in glucose metabolism may be observed across ALS disease models.…”
Section: Alterations In Glucose Transport or Utilizationmentioning
confidence: 99%
“…A similar observation was previously described by Miyazaki et al [ 38 ], who showed that in the spinal cord of SOD1-G93A mice, glucose metabolism appeared to be reduced at early symptomatic and end stages of the disease but was increased before disease onset. Recently, another study used simultaneous [ 18 F]-FDG PET magnetic resonance imaging and showed that glucose metabolism is decreased in the motor and somatosensory cortices of TDP-43 (A315T) mice, while at the same time, it was increased in the midbrain region between at pre-symptomatic age, as compared to WT controls [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of ALS on metabolic function in humans and animal models of ALS are yet to be fully understood. In animals, one study has measured the glucose uptake in the brains of mice carrying the human TDP-43 A315T mutation [4]. The authors observed a significant hypometabolism in motor and somatosensory cortex, as well as a hypermetabolism in amygdala and brainstem.…”
Section: Main Textmentioning
confidence: 99%